Cattle productive performance evaluation confined submitted immunocastration - Maluf, J. M.; Souza, T. V.; Moreira, P. S. A. (Scientific Electronic Archives, 2016)
In order to evaluate the performance and carcass characteristics of cattle cross breeds ½ Aberdeen Angus x ½Nelore and Nelore confined submitted to immunocastration 218 male animals were used, feedlot, averaging 342 kg, divided into three experimental groups, T1: 117 steers ½ Angus x ½ Nelore no castrated (ANC), T2: 51 Nelore steers uncastrated (NNC) and T3: 50 Nellore steers immunocastrated (NIC). The experiment lasted 144 days of confinement. The selection of animals for group formation was according to the individual weight, breed, sex condition and age. For immunocastration it wasused Bopriva® vaccine. The rating was finished according to the parameter used by the meatpacking industry ranging from 1 to 5. The experimental design was completely randomized in three groups. For the analyzes the variables studied statistics were submitted to analysis of variance (ANOVA) and Tukey test both at the 5% level of significance. The results showed differences (p <0.01) at various features of productive performance and carcass between treatments. For slaughter weight, the ANC animals were higher (with 582.1 kg) to Nelore, regardless of sexual condition, and the NNC were in turn heavier than the NIC, 527.4 and 503.7 respectively. Finally, it observed that the use of immunocastration in Nellore animals provided a decrease in productive performance of confined animals, but provided better finish carcass similar to crossbred (ANC).